Inevitable Landmarks for Inclination of Occlusal Plane in Completely Edentulous Patients- A Literature Review - Kumar, C. Dhinesh; Sunantha, S.; Mohan, Jayashree (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Background: The establishment of the occlusal plane is a very important facet in conventional prosthodontic rehabilitation to restore the occlusal contact to the original condition with the ambience of a harmonious stomatognathic system. The ideal position of artificial teeth in complete denture in the same position of natural teeth will be achieved by the orientation of occlusal plane similar to the natural location of the occlusal plane. This review highlights the basic concepts and significance of the occlusal plane, it also evaluates various anatomical landmarks associated with the orientation of the occlusal plane to achieve the functional, mechanical and esthetic rehabilitation of completely edentulous patients with various treatment options like a conventional complete denture, maxillofacial prosthesis and implant-supported prosthesis. Conclusion: This literature review unveils the mystery of orientation of occlusal plane for completely edentulous patients by using the anatomical landmarks and reference planes. Such scientifically established plane of occlusion provides biofunctional occlusion.